Genomic evolution, antimicrobial resistance, and dissemination of global Serratia spp. unveil increasing species diversity and carbapenemae‑resistance: A retrospective and genomic epidemiology study - Wentao Zhu; Xi Chen; Hong Shen; Ming Wei; Li Gu; Qian Liu (Current Research in Microbial Sciences)
Serratia spp., an opportunistic pathogen, has increasingly acquired resistance, particularly the emergence of carbapenemase-resistance. However, previous studies have focused on fragmented surveillance and have not conducted overall correlation. Here, 3769 non-duplicate Serratia genomes from sixty-five different countries across seven continents were classified into thirty-seven bacterial species, with 14 novel genospecies. The most common species was S. sarumanii, followed by S. nevei and S. marcescens. 809 novel STs were determined, which was more than double the number of known STs, with ST 367 and ST324 being the most predominant. 26.6 % (1001/3769) of Serratia isolates were carbapenemase-resistant. These resistant isolates were first identified in 1970, sporadically detected before 2010, and have increased rapidly since 2011. Carbapenemase-resistant isolates were found in 46 countries, with the most prevalent being in the USA (41.2 %), China (9.9 %), Australia (7.6 %). 34 carbapenemase-encoding genes were reported, with the most common being blaKPC-2 (25.7 %), blaSPR-1 (19.2 %), blaKPC-3 (10.1 %). 94 potential transmission events were identified from 24 countries, including five cross-country events. The largest epidemic clone of 99 isolates (ST324) was detected in USA, with longest lasting transmission event spanning 17 years and involving 15 isolates (ST893) from Australia. The overall incidence of MDR isolates was 61.6 %. The prevalence of carbapenemase genes associated with specific STs. 248 IS types and 61 plasmid replicons were identified in carbapenemase-resistant Serratia isolates, with varied IS or plasmid replicons being responsible for the spread of different carbapenemase genes. This comprehensive genomic study offers valuable insights into the population dynamics, prevalence and distribution of Serratia.